(untitled) (Fiep Bulletin - online, 2015)
The pressure on the floor caused by a man making different movements, can means of a strain gauge arrangement. We have a platform made of plastic fibers, length 1,50 m. A man moves from a standing position to a position with bent knees. The force-time curve is registered, by rising again you get the last of the curve.